Immune targets to stop future SARS-CoV-2 variants - Milena Silva Souza; Jéssica Pires Farias; Wilson Barros Luiz; Alexander Birbrair; Ricardo Durães-Carvalho; Luís Carlos de Souza Ferreira; Jaime Henrique Amorim (Microbiology Spectrum, 2023)
ABSTRACT The SARS-COV-2 variants of concern (VOCs) accumulated mutations that confer to the viral particle a higher infectivity as well as a capacity to escape neutralizing antibodies (NAbs) elicited by vaccines. In this study, we aimed to identify immune determinants that can be targeted to control future SARS-CoV-2 VOC. Using an immunoinformatics pipeline, we constructed a first data set consisting of 215 spike (S) protein amino acid sequences of the wild-type SARS-CoV-2, as well as of the Alpha, Beta, Delta, Gamma, and Omicron variants/subvariants (BA.1, BA.2, BA.4, BA.5, XBB, and BQ.1). A second data set was composed of epitope amino acid sequences for NAb as well as for T-cells involved in anti-viral activity, retrieved from the Immune Epitope Database (IEDB). Epitope conservation and population coverage analyses were carried out using the data sets. The localization of fully conserved epitopes in the S protein was performed using PyMOL. As main results, (i) fully conserved epitopes were identified: 28 for NAbs and 53 and 99 for class-I and class-II human leukocyte antigen, respectively; (ii) the fully conserved epitopes were shown to have high coverage in the world population (99.77% class combined); and (iii) the receptor-binding domain (RBD) of the S protein better balanced numbers of epitopes for NAb and T-cells, while the subunit two concentrated the highest numbers of T-cell epitopes. These results indicate that the RBD region holds different kinds of immune targets that could be used in an escape mutation-proof vaccine antigen to control future SARS-CoV-2 variants. IMPORTANCE The emergence of SARS-CoV-2 had a major impact across the world. It is true that the collaboration of scientists from all over the world resulted in a rapid response against COVID-19, mainly with the development of vaccines against the disease. However, many viral genetic variants that threaten vaccines have emerged. Our study reveals highly conserved antigenic regions in the vaccines have emerged. Our study reveals highly conserved antigenic regions in the spike protein in all variants of concern (Alpha, Beta, Gamma, Delta, and Omicron) as well as in the wild-type virus. Such immune targets can be used to fight future SARS-CoV-2 variants.